Revealing grain boundary kinetics in three-dimensional space - Chen, Yingbin (2024)
Grain boundaries (GBs) in polycrystalline and nanocrystalline materials are rarely flat, and their curvatures often evolve dynamically in three-dimensional (3D) GB network under thermomechanical stimulations. However, the complexity of polycrystalline microstructure greatly hinders our understanding of GB kinetics with 3D crystallographic clarity, especially at atomic scale. Here, we reveal a disconnection-based mechanism of GB kinetics in 3D space, by combining atomic-resolution in situ nanomechanical testing and atomistic simulations. Upon loading, GB can gradually adjust its curvature in 3D via sequential nucleation, propagation and annihilation of curved disconnections, where anisotropic mobilities of different disconnection segments induce a dynamic GB curving in 3D. Such curved disconnection-mediated GB curving and migration can coordinate among multiple GBs, and contribute to 3D grain growth/annihilation in GB networks. This curved disconnection-based 3D GB kinetics elucidates a long-elusive perspective in GB deformation, significantly advancing current knowledge of GB-mediated plasticity in metallic materials.